1996
DOI: 10.1021/jm9509096
|View full text |Cite
|
Sign up to set email alerts
|

Novel Selective PDE IV Inhibitors as Antiasthmatic Agents. Synthesis and Biological Activities of a Series of 1-Aryl-2,3-bis(hydroxymethyl)naphthalene Lignans

Abstract: A series of 1-aryl-2,3-bis(hydroxymethyl)naphthalene lignans have been synthesized and evaluated for their ability to selectively inhibit PDE IV isolated from guinea pig. Replacement of the 1-phenyl ring by a pyridone ring led to marked improvement of their selectivity for PDE IV over PDE III. The compounds that were most potent and selective involved those bearing an N-alkylpyridone ring at C-1. These compounds also showed potent antispasmogenic activity without causing significant changes in heart rate in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 16 publications
1
39
0
Order By: Relevance
“…This effect was statistically significant at 3 mg/kg, but was very weak. These results are supported by our previous data that the effect of T-440 to inhibit PDE III purified from guinea pig heart was 1000 times less potent than that to inhibit PDE IV from the lung (15). In addition to PDE IV, PDE III was also reported to regulate the intracellular cAMP level of the airway smooth muscle, and PDE III inhibition also produced bronchodilation (22).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…This effect was statistically significant at 3 mg/kg, but was very weak. These results are supported by our previous data that the effect of T-440 to inhibit PDE III purified from guinea pig heart was 1000 times less potent than that to inhibit PDE IV from the lung (15). In addition to PDE IV, PDE III was also reported to regulate the intracellular cAMP level of the airway smooth muscle, and PDE III inhibition also produced bronchodilation (22).…”
supporting
confidence: 82%
“…T-440 was elaborated during a search for an anti-asthma drug. We previously reported that this drug selectively inhibited the activity of PDE IV purified from the guinea pig lung (15). Now, detailed pharmacological studies revealed that T-440 displayed the inhibitory effect on the bronchoconstriction produced by antigen and chemical mediators in anesthetized guinea pigs.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…[1][2][3][4][5] A literature survey revealed that most 2-phenylbenzofurans with hydroxy and methoxy groups demonstrated multi-bioactivities, including antitumor, 6,7) anti-microbial, [8][9][10] antivirus, 11) adenosine A 1 receptor antagonists 12,13) and immunosuppressant properties. 14) In recent years, it is found that 2-phenylbenzofurans have significant binding affinity and selectivity on estrogen receptor (ER)β. 15) Here, we reported an improved synthetic method for 2-phenylbenzofurans 5a-g from 3-phenylcoumarins 3a-g. After purification, these compounds were evaluated for ER binding affinity and selectivity in vitro.…”
mentioning
confidence: 99%
“…We previously re ported that T-440 inhibited PDE IV purified from guinea pig lung with IC50 o f 0.057 pAf, but not PDE 1, II, III and V even at 10 \kM [28]. T-440 administered in vivo inhibited antigenand chemical mediator-induced bronchoconstriction [29], The effect of T-440 correlated closely with the inhibitory activity against PDE IV purified from guinea pig lung [28], Additionally, treatment with T-440 in vitro inhibited cyto kine production by T cells accompanied by the suppression o f cAMP-PDE activity and increase in intracellular cAMP [30], This study strongly supports these previous results as T-440 suppressed IAR, LAR and airway eosinophil accu mulation.…”
Section: Introductionmentioning
confidence: 98%